UJI AKTIVITAS EKSTRAK ETANOL 96% DAN FRAKSI DAUN KIRINYUH (Chromolaena odorata L.) TERHADAP PROPIONIBACTERIUM ACNES - Oom Komala; Yulianita .; Rita Rahmawati (Universitas Pakuan, 2021)
Chromolaena odorata L. leaves can be used as an antibacterial because of contain flavonoid compounds. The secondary metabolite content of Chromolaena odorata L leaves include flavonoids, tannins, saponins, and steroids which have antibacterial activity. The aim of this study was determine the antibacterial activity of ethanolic 96% and fraction of Chromolaena odorata L leaves and determine the concentration of Chromolaena odorata L fraction and ethanol 96% extract which was most effective as an antibacterial against Propionibacterium acnes. The method was used to determine the MIC was a solid dilusion method, while the determination of inhibitory zone by the paper disk diffusion method at concentrations of 10%, 15% and 20% in each sample. The MIC showed hexane fraction is 15%, ethylacetate fraction is 15% and water fraction is 10%. The best antibacterial activity in the ethylacetate fraction and ethanol 96% extract at a concentration of 20% with the width of the zone of inhibition values of 4.375 mm and 4 mm.